ANALISIS TINGKAT KESEHATAN KEUANGAN PADA PERUSAHAAN ASURANSI GO PUBLIC DI BURSA EFEK INDONESIA - Putra, Klanisto Raka; Trisnaningsih, Sri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study is to identify and understand the effect of Risk Based Capital(RBC), Investment Ratio, Claim Ratio, and Premium Growth Ratio on increasing premiumincome in insurance companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. This study uses quantitative research that refers to financial data and other datafrom IDX database and the company's official website to find out the company's financialstatements for 2016-2020. Data collection techniques using the method of documentationand literature study. The focus of this research is the level of financial soundness ofinsurance companies that go public on the IDX in 2016-2020. The results of this studyindicate that RBC and Premium Growth Ratio have a positive effect on increasingpremium income in insurance companies listed on the IDX in 2016-2020. While theInvestment Ratio (ROI) and claims ratio do not have a positive effect on increasingpremium income in insurance companies listed on the IDX in 2016-2020. Meanwhile,RBC, Investment Ratio (ROI), Claim Ratio, and Premium Growth have a simultaneouspositive effect on the increase in Premium Income in insurance companies listed on theIndonesia Stock Exchange (IDX) in 2016-2020.